An autopsy of the coloniality of suicide: Modernity's completed genocide. (January 2022) - X, Tisha; polanco, marcela
From the Latin American modernity/coloniality project, we address the inhospitality of the modern/colonial and globally designed world-system in relation to suicidality. In our vernacular Spanglish, guided by epistemological disobedience, and responding to epistemicide, we interpellate ourselves to unmask the hidden colonial structures of power of modernity's global design on suicide knowledge. Our intent is to argue, specifically from the perspective of coloniality and our racialized, gendered, and monetized bodies, that suicide is rather an extension of modernity's colonial genocide. From the decolonial geo and body-politics of knowledge, our discussion on modernity's Eurocentric rhetoric on suicide departs from the materialization of suicidality in our flesh. We story experiences of our bodies with life and pleas of death, within the context of our immigrant backgrounds, and as family therapists in the United States (U.S.). We adopt autopsy as an analogy from where to advance such analysis to contest Eurocentric configurations of suicide from within, but against modernity. We emphasize the hidden racism and capitalism of suicide embedded within the persuasive Eurocentric promises of the Anglo scientific method and the U.S. American Dream. We address the concepts of epistemicide, coloniality of knowledge and of being. It is our hope to contribute to further advance decolonizing possibilities to reinscribe options that would border with the current Western knowledge on suicide. This may require other configurations of the body, knowledge, hence ways of being, doing, thinking, sensing, feeling, imagining, and dreaming to coexist among pluriversal hospitable worlds of life and death.